Aerodynamic Performance of Propellers for Multirotor Unmanned Aerial Vehicles: Measurement, Analysis, and Experiment - Hang Zhu; Zihao Jiang; Hang Zhao; Siyu Pei; Hongze Li; Yubin Lan (Shock and Vibration)
Analyzing the propeller aerodynamic performance is of vital importance for research and improvement of unmanned aerial vehicles. This paper presents the design requirements for a propeller for rotorcraft unmanned aerial vehicles and an analysis of a model for calculating propeller aerodynamic performance. Based on blade element momentum theory, the aerodynamic force of a blade element is analyzed and used. The symmetric airfoil NACA 0012 is used as an example to verify the validity of the model. An experimental system for propeller aerodynamic performance is designed and built to test the aerodynamic performance of six types of the propeller from a single manufacturer (APC). Data-processing software is also developed to draw curves and perform single-step calculations of three propellers’ parameters: airfoil resistance power, induced velocity, and efficiency. The results of the experiment indicate that both the thrust and torque of the propeller increase with rotational speed, propeller diameter, and propeller pitch. The research is of great significance to select more suitable propellers for unmanned aerial vehicles and the further improvement of the performance of unmanned aerial vehicles’ dynamical system.